2021
DOI: 10.1080/0284186x.2021.1876246
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic factors in pleural mesothelioma: best supportive care and anti-tumor treatments in a real-life setting

Abstract: Background: This study aims to investigate patient-and disease characteristics associated with survival in malignant pleural mesothelioma (MPM) patients with anti-tumor treatment or with best supportive care (BSC). Materials and methods: Consecutive MPM cases diagnosed in North Denmark Region from 1972 to 2015 were reevaluated and verified by two pathologists using modern immunohistochemical techniques. Danish registries and hospital records were used to gather patient-, asbestos exposure-, and disease informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Finally, it should be noted that a retrospective study revealed that adjuvant treatment with gemcitabine improves survival in K. pneumoniae-negative pancreatic cancer patients, whereas adjuvant treatment with quinolones (which are bactericidal) was associated with better overall survival (OS). This result suggests that the presence of K. pneumoniae may promote chemoresistance to adjuvant gemcitabine in pancreatic cancer (45). Taken together, is evident that the wider literature supports the negative impact Klebsiella has on patients, which is consistent with our finding that Klebsiella was more abundant in Low Survivors than High Survivors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, it should be noted that a retrospective study revealed that adjuvant treatment with gemcitabine improves survival in K. pneumoniae-negative pancreatic cancer patients, whereas adjuvant treatment with quinolones (which are bactericidal) was associated with better overall survival (OS). This result suggests that the presence of K. pneumoniae may promote chemoresistance to adjuvant gemcitabine in pancreatic cancer (45). Taken together, is evident that the wider literature supports the negative impact Klebsiella has on patients, which is consistent with our finding that Klebsiella was more abundant in Low Survivors than High Survivors.…”
Section: Discussionsupporting
confidence: 91%
“…Further to the above, the identification that epithelioid histology was a significant prognostic indicator compared to other variables has evidence in the literature ( 46 ). As Petersen and colleagues published in 2021, epithelioid histology was the only positive independent prognostic factor for treated pleural mesothelioma patients ( 46 ). In this patient cohort, neither age nor gender nor stage were significant by univariate analysis for overall survival (OS).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a result, their prognosis may be better, consistent with a previous study ( 34 , 35 ). However, whether age affect the prognosis of patients is still controversial ( 36 , 37 ). This result should be validated in subsequent large-sample studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although survival following diagnosis is relatively short, 10 a small number of long survivors have been reported. 10,69,70 A few prognostic scoring systems have been proposed to predict survival in mesothelioma patients [71][72][73] but these remain suboptimal.…”
Section: Discussionmentioning
confidence: 99%